Evaluation Some of the Physical Properties of Poly Methyl Methacrylate-Zirconium Oxide Nanocomposite Denture Base Material - Yazan Hussam Al-D; Ammar Khalid Al-Noori (University of Mosul, College of Dentistry, 2023)
Aims: the current study aimed to add two concentrations of zirconium oxide nanoparticles (1.0 percent and 2.0 percent) to "heat-cured PMMA" in order to improve its characteristics such as transverse strength and impact strength. Materials and Methods: The particle size of Zirconium Oxide ZrO2 is 20nm. The ZrO2 nanoparticles were added to the "heat-cured PMMA" resin base at 1.0 percent and 2.0 percent by weight, respectively, to create a PMMA-ZrO2 nanocomposite of two various percentages to compare to PMMA without additives. For the transvers strength test and impact strength test, the traditional heat-curing technique was used with a water bath to polymerize the specimens. The data of the study were evaluated using a one-way ANOVA and a Duncan multiple range test with a significant P-value of (0.05). Results: An increase in transversal and impact strength for PMMA-ZrO2 nanocomposite of 1.0 and 2.0 percentages was noticed after comparison of the findings at (p0.05). Conclusion: By using Zirconium Oxide nanoparticles as dental filler at 1% and 2% by weight, the transverse strength and impact strength of PMMA denture base material were enhanced.